Istishab dan Penerapanya dalam Hukum Islam - Ridwan, Ridwan (Al-Manahij: Jurnal Kajian Hukum Islam, 2011)
Development of modernization marked by the emergence of globalization has spawned highly complex problems of Islamic law that requires Muslims to exercise ijtihad in order to make Islamic law could be adapted in the spectrum of modern culture. This article wants to prove that istishab can be used as an alternative method of ijtihad in answering legal problems of contemporary Islam. Ijtihad is the inner-dynamic for the emergence of changes to safeguard the ideal of universality of Islamic teachings as a system that salihun li kulli zaman wa-l makan. istishab is a method of law invention based on pre-existing law as long as there are no arguments (legal evidence) which indicate otherwise. To prove the thesis above, some cases in criminal, civil and marriage laws are presented as samples.